P-192 Taking inpatient unit level care into the home: auto-ethnographic reflections of two hospice doctors. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Thomas, H Lucy; Cooper, Helen
Abstract : Background: In November 2016, building work required us to temporarily reduce the number of our hospice inpatient beds and modify our model of care. We transitioned from having a 12-bed inpatient unit (IPU), to five inpatient beds complemented by four 'enhanced hospice at home' beds providing inpatient-level care to end of life patients with complex needs in their own homes. This included providing up to one medical home visit a day as part of a multidisciplinary team. Aim: In this presentation, we reflect on the impact on our doctoring role of shifting the location of complex end-of-life care from the professional setting to the intimacy of the patient's home. Methods: We used an auto-ethnographic (Chang, 2016) approach to create and analyse written reflections on caring for six patients in the IPU and enhanced hospice at home setting. Based on our analyses, we will present our findings as an illustrative story of caring for one patient and their family. Results: We identified four key themes: Fulfilling the promise to provide continuity of care (Leadership Alliance for the Care of Dying People, 2014): 'We'll be there for you until the end [and I mean it].' Dissolving professional boundaries within the multidisciplinary team (Hospice UK, 2015): 'Working together, side by side.' Supporting rather than supplanting existing care (Janssen & MacLeod, 2012): 'Thank you for helping us care for him.' Shifting the boundaries between care-giver and care-receiver (Janssen & MacLeod, 2012): 'Would you like a cup of tea doctor? You must find it difficult dealing with all this loss ….' Conclusions: Changing location from a professional setting in which we deliver care, to a home setting into which we are invited as co-carers has the potential to redefine our relationships with our patients, their families and our colleagues. It can enable us to support, rather than supplant reciprocal caring relationships (Janssen & MacLeod, 2012), embrace national palliative care initiatives (Leadership Alliance for the Care of Dying People, 2014; Thomas et al., 2016), and through increased job satisfaction build our professional resilience (Hospice UK, 2015).